Risk Factors Associated with Injury and Mortality from Paediatric Low Speed Vehicle Incidents: A Systematic Review - Anne Paul Anthikkat; Andrew Page; Ruth Barker (International Journal of Pediatrics)
Objective. This study reviews modifiable risk factors associated with fatal and nonfatal injury from low-speed vehicle runover (LSVRO) incidents involving children aged 0–15 years. Data Sources. Electronic searches for child pedestrian and driveway injuries from the peer-reviewed literature and transport-related websites from 1955 to 2012. Study Selection. 41 studies met the study inclusion criteria. Data Extraction. A systematic narrative summary was conducted that included study design, methodology, risk factors, and other study variables. Results. The most commonly reported risk factors for LSVRO incidents included age under 5 years, male gender, and reversing vehicles. The majority of reported incidents involved residential driveways, but several studies identified other traffic and nontraffic locations. Low socioeconomic status and rental accommodation were also associated with LSVRO injury. Vehicles were most commonly driven by a family member, predominantly a parent. Conclusion. There are a number of modifiable vehicular, environmental, and behavioural factors associated with LSVRO injuries in young children that have been identified in the literature to date. Strategies relating to vehicle design (devices for increased rearward visibility and crash avoidance systems), housing design (physical separation of driveway and play areas), and behaviour (driver behaviour, supervision of young children) are discussed.